Peningkatan Kualitas Ayam Ras Pedaging Pada CV Banda Poultry Shop Bandung: (The Increase In Broiler Quality Through Closed House Cages Construction On CV Banda Poultry Shop Bandung - Muhammad Dicky S; Wien Kuntari (IPB University, 2017)
ABSTRACT The purpose of development for this business to formulate the idea of business development by increasing the quality of broiler chickens using a closed house cage at CV Banda Poultry Shop based on financial and non financial aspects. The idea of business development comes from current issues that broiler mortality was relatively high (6%), and the chickens’ weight is too varied. The business development plan that will be executed is replacing the enclosure of the open-house system into closedhouse. Aim to reduce the level of mortality and improve the uniformity of broiler’s weight, this business development is supported by the availability of technology that can help broiler farming process to be more effective and efficient. This business development is using the same organizational structure, will only add three new workers. Based on financial analysis, this business development has the values of NPV Rp 23 659 722 209.6, IRR 46 percent, Net B/C 3.80 and payback period for 5 years and 6 months. Based on those financial and non financial aspects, the business development is feasible. Based on the switching value analysis, company is sensitive to the changes in the decrease of broiler production by 11.06 percent and company isn’t sensitive to the changes in the increase DOC broiler price by 59.49 percent. The solutions to rise the price of DOC are by changing the brand of DOC (still has good quality) or making hatchery division in the company. Then, when the selling price of chicken is down, the company can sell the chickens in the form of carcasses or make the chickens meat processing industry.